2020
DOI: 10.2217/lmt-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Humanistic Burden of Living with Anaplastic Lymphoma Kinase-Positive Non-Small-Cell Lung Cancer: findings from the ALKConnect Patient Insight Network and Research Platform

Abstract: Aim: Evaluate real-world patient preferences, experiences and outcomes (health-related quality of life [HRQoL]) from patients with anaplastic lymphoma kinase-positive (ALK+) non-small-cell lung cancer (NSCLC) utilizing the ALKConnect Patient Insight Network. Patients & methods: Demographics, disease history/status/treatment, patient preferences and HRQoL (MD Anderson Symptom Inventory lung cancer module, reported as symptom severity and interference) were evaluated for US adults with ALK+ NSCLC. Results: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Our finding of a labor market affiliation for working age (<60 years of age) ALK+ NSCLC patients of 36% 18 months following diagnosis thus compares very well with previous findings both among lung cancer patients in general [ 10 , 33 , 34 ], among lung cancer patients treated with targeted agents at large [ 35 ], and among patients with ALK+ NSCLC specifically [ 36 ]. Our results thus suggest that ALK+ NSCLC patients when assessed according to labor market affiliation currently do not comprise a distinct subgroup of lung cancer patients, despite their superior survival and lessened toxicity burden.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our finding of a labor market affiliation for working age (<60 years of age) ALK+ NSCLC patients of 36% 18 months following diagnosis thus compares very well with previous findings both among lung cancer patients in general [ 10 , 33 , 34 ], among lung cancer patients treated with targeted agents at large [ 35 ], and among patients with ALK+ NSCLC specifically [ 36 ]. Our results thus suggest that ALK+ NSCLC patients when assessed according to labor market affiliation currently do not comprise a distinct subgroup of lung cancer patients, despite their superior survival and lessened toxicity burden.…”
Section: Discussionsupporting
confidence: 89%
“…One study reported that 25% of a small cohort (N = 20) of patients with metastatic lung cancer treated with PD-L1 inhibitors and tyrosine kinase inhibitors from a single institution in Australia were employed following lung cancer diagnosis (median time 27 months) [ 35 ]. The other, larger study used an online survey specific for patients with ALK+ NSCLC in the US and found a labor market affiliation of 40% among 104 patients 25.6 months (median) after diagnosis [ 36 ]. 25% of the patients surveyed in this study matched our definition of working age (<60 years of age), and the majority (77%) of the patients had metastatic or regionally spread disease [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation